Epidemiological Features of an Infertile Male Population - Kanat Pektaş, Mine; Günel, Müfit; Güngör, Tayfun (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: This research aims to identify the epidemiological features of Turkish men who seek medical help for their childlessness. STUDY DESIGN: 474 men attending to the out-patient urology clinics of our hospital between January 2005 and January 2006 were questioned in aspects of age, fertility, occupation, chronic diseases, surgical history, trauma, and drug usage, smoking, alcohol intake, substance abuse and exposure to gonadotoxins. RESULTS: The majority of the participants were 25 to 35 year-old Caucasian men who had primary infertility. 91.4%, 98.3%, 87.6% of these subjects did not reveal any disease, trauma and drug usage associated infertility. 41.1% of the study population had scrotal operations. %62.9 of these participants was smokers yet only 7.6% of them consumed alcohol. Although %67.7 of the patients did not have any jobs that might be associated with infertility, 32.9 % of patients were exposed to occupational gonadotoxins; mostly heat. 10.8% and 8.0% of the study population were drivers and farmers exposed to heat and pesticides respectively. CONCLUSION: Many childless men represent as young males who are at obvious risk due to congenital and acquired genital abnormalities and silent exposure to environmental and occupational hazards. Men chronically exposed to heat and pesticides due to either sedentary or agricultural work are considered to be at utmost risk for infertility.